A SECRET COMPONENT IN ARCHITECTURAL DESIGN STUDIO: THE FILTERING CONCEPT - Yurtsever, Bengi; Polatoglu, Cigdem (OPEN HOUSE INT, 2018)
Learning is an internalization process that depends on individual components. This study focuses on the problematic of learning in architectural design education process and examines its components. The relationship between learning and perception and how it can be handled in the architectural environment is discussed. Answers are searched on the axis of individual, experience, perception and especially is focused the concept of filtering. The learning environment in the architectural design studio is seen as a cultural environment where all actors share their experiences. It is thought that these variables should be brought to the forefront in order not to lose the originality, with so many variables connected with these cultural actors. In this context, it is aimed to examine the relation between filtering and authenticity in the process of debating the problem of learning in working. The discussion was conducted through a blended learning environment that is supposed to support the aforementioned relationship. The study is based on the constructing grounded theory as a qualitative research pattern. The dynamic structure that can be empowered by the field experience of the selected research pattern has been a driving force in the study. Temporary hypotheses were identified with the preliminary problems and conceptual samples that were expected to be discussed, and then an experience environment was created that could generate data for the study. Then an experience environment was created that could generate data for the work. The implications of the observations, the open-ended questionnaires and the process of making the interviews were evaluated by descriptive analysis. With this approach, problems can be observed on an individual basis; and some of the problems that were grounded were brought into questionable positions with the architectural design studio.
Keywords: Architectural Design Education; Filtering; Blended Learning; Studio Culture; Constructing Grounded Theory; Architecture; Environmental Sciences & Ecology; Urban Studies